2016
DOI: 10.1109/tia.2016.2563391
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Driven Addressing of Oil-in-Water Droplets in the Presence of Gradients of Ionic and Nonionic Surfactants

Abstract: We deal with controlled transport (addressing) of dielectric kerosene droplets dispersed on water surface by DC electric field in the presence of surfactants. Experimental planar microfluidic platform with a central chamber and two electrode compartments enables formation of concentration gradients of cationic, anionic or nonionic surfactants. We show that a kerosene droplet always moves away from the surfactant reservoir due to the Marangoni phenomenon. The release of ionic surfactants can be well controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…As was alluded to in the previous section, there are a large variety of parameters that have an influence on the EP mobility of droplets. These parameters include the surface charge of the droplet [36, 76, 87, 88], pH [89], internal flow in the droplets [41, 44, 65, 78], the viscosity ratio of the dispersed and continuous phase [44, 57], droplet size, surface charge of the channel wall [44, 90], electric field strength, [73, 91–93], as well as the boundary effects [44]. A generalized summary of the effect of these parameters on the droplet EP mobility and velocity is shown in Table 1, together with potential methods to measure these parameters.…”
Section: Parameters Influencing Droplet Ep Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…As was alluded to in the previous section, there are a large variety of parameters that have an influence on the EP mobility of droplets. These parameters include the surface charge of the droplet [36, 76, 87, 88], pH [89], internal flow in the droplets [41, 44, 65, 78], the viscosity ratio of the dispersed and continuous phase [44, 57], droplet size, surface charge of the channel wall [44, 90], electric field strength, [73, 91–93], as well as the boundary effects [44]. A generalized summary of the effect of these parameters on the droplet EP mobility and velocity is shown in Table 1, together with potential methods to measure these parameters.…”
Section: Parameters Influencing Droplet Ep Mobilitymentioning
confidence: 99%
“…The surface charge of a droplet can be measured using standardized ζ‐potential measurements. The surfactant type in the system [76, 88], or the nature of the interface‐stabilizing nanoparticles [94, 95], pH [12, 38, 87], and ionic strength of the solution [96, 97] are contributing factors to the apparent surface charge or ζ‐potential at the droplet interface.…”
Section: Parameters Influencing Droplet Ep Mobilitymentioning
confidence: 99%
“…Tuček et al reported electric-field-controlled kerosenedroplet transport on a water surface containing surfactants. [63] Controlling the concentration gradients of the ionic surfactants by an electric field was critical in the transport process. The kerosene droplet was pushed away from the direction of the surfactant reservoir owing to Marangoni flow, which is different from classical electrophoretic migration.…”
Section: Electric-field-induced Directional Liquid Motionmentioning
confidence: 99%
“…We recently avoided this problem by employing dc electric field to gradually release ionic surfactants from a reservoir into a system, in which no surfactant molecules are initially present. In that study, a dielectric droplet was placed on the surface of DI water . The released molecules of surfactants formed a gradient of surface tension, which was successfully used for controlled displacement of dielectric droplets.…”
Section: Introductionmentioning
confidence: 99%